Caractéristiques socio-économiques d’une intégration régionale en Amazonie colombienne (région de Florencia, Caqueta) - Xavier Arnauld de Sartre; Johan Oszwald; Berta Ramírez; Gamaliel Rodríguez; Jaime Velazquez; Pascal Sebille; Patrick Lavelle (Caravelle)
The colonization of the Colombian Amazon is associated with the CO3 model (Colombia, Coca, Colonization, first established by O. Dollfus) and political violence. Through a survey of farmers of a former CO3 region (around Florencia, Caqueta departement), we study the evolution of this kind of region. Following a brief summary of the history of this region, we analyze the characteristics of these populations and the main productions of their farm, which are compared with those of an active frontier in the Brazilian Amazon.